Unilateral Interstitial Lung Disease with Contralateral Effusion: Unusual Case Report of Dasatinib Toxicity - Bhaskar, Maheema; Biraris, Pavankumar; Tisekar, Owais; Kaushal, Rajiv Kumar; Janu, Amit; Tandon, Sandeep (Indian Journal of Medical and Paediatric Oncology, 2022)
Dasatinib is a second-generation tyrosine kinase inhibitor (TKI) used in chronic myelogenous leukemia (CML). While pleural effusion due to Dasatinib is well described in the literature, interstitial lung disease (ILD) caused by it is rare. A 60-year-old gentleman was on treatment with 100 mg of tablet Dasatinib per day for chronic myeloid leukemia. He presented to the outpatient department with history of progressive breathlessness over 2 months. High-resolution computerized tomography (HRCT) thorax revealed mild right-sided effusion and non-specific interstitial pneumonia (NSIP) pattern of ILD in the left lower lobe. Thoracocentesis of the right-sided pleural effusion showed exudative and lymphocytic rich pleural effusion. The effusion was negative for malignant cells or infection. Biopsy of the left lower lobe was consistent with the diagnosis of ILD. He was started on prednisolone which was gradually tapered and stopped. At 3 months, there was a complete resolution of the ILD and pleural effusion. Clinicians need to be aware about the pleuroparenchymal toxicities of Dasatinib. Early diagnosis and treatment with steroids can lead to complete resolution of the signs and symptoms.
Keywords: Dasatinib; interstitial lung disease; prednisolone; chronic myelogenous leukemia